2001
DOI: 10.2175/106143001x143457
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Enteric Microorganisms at the Upper Occoquan Sewage Authority Water Reclamation Plant

Abstract: The Upper Occoquan Sewage Authority (UOSA) Water Reclamation Plant, Centreville, Virginia, is a state-of-the-art wastewater treatment plant that was created to treat area wastewater and provide protection for the Occoquan Reservoir. This study investigated UOSA's unit processes as barriers to pathogenic as well as alternative and traditional indicator microorganisms. Samples were collected once a month for 1 year from eight sites within UOSA's advanced wastewater reclamation plant. The eight sites were monitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…The net outcome of the STP treatment process is recycled water with a reduced number of bacteria and, ideally, no pathogens (15). In a typical STP, the bacterial count is normally reduced by 90% (27,35); however, studies by Harwood et al (15) and Kay et al (18) have shown that approximately 67% of the initial number of total coliforms present in the primary and/or secondary sedimentation effluent can still be detected in disinfected tertiaryeffluent samples (15,18). Moreover, organisms with high initial concentrations (in influent) can still be retained at detectable levels in disinfected effluents.…”
Section: Discussionmentioning
confidence: 99%
“…The net outcome of the STP treatment process is recycled water with a reduced number of bacteria and, ideally, no pathogens (15). In a typical STP, the bacterial count is normally reduced by 90% (27,35); however, studies by Harwood et al (15) and Kay et al (18) have shown that approximately 67% of the initial number of total coliforms present in the primary and/or secondary sedimentation effluent can still be detected in disinfected tertiaryeffluent samples (15,18). Moreover, organisms with high initial concentrations (in influent) can still be retained at detectable levels in disinfected effluents.…”
Section: Discussionmentioning
confidence: 99%
“…Comparisons of UV disinfection efficacies on a seeded laboratory strain of E. faecalis versus environmental isolates indicated that the former is more resistant (57,156,222). Meta-analyses of the existing literature indicated that chlorine disinfection considerably outperforms UV radiation in reducing concentrations of enterococci by as much as 2 orders of magnitude (58,152,182,272,273) (Table 2).…”
Section: Responses To Environmental Stressorsmentioning
confidence: 99%
“…In tropical regions, contamination of surface water increases during wet seasons. Although spread of pathogens via food is certainly possible, contaminated water is the dominant source of exposure for enteric infections caused by protozoa Cryptosporidium and Giardia (10)(11)(12). Depending on locality, outbreaks of cryptosporidiosis and giardiasis associated with drinking or recreational water frequently occur during warm or wet seasons (13,14).…”
Section: Seasonality In Pathogens Survival and Transmissibilitymentioning
confidence: 99%